A New Tool for CRISPR-Cas13a-Based Cancer Gene Therapy - Jinliang Gao (Molecular Therapy: Oncolytics, 2020)
Cas13a has already been successfully applied to virus detection. However, as a new gene interference tool, its potential in cancer treatment was not fully explored until now. This study constructed a new Cas13a expression vector, decoy minimal promoter-Cas13a-U6-guide RNA (DMP-Cas13a-U6-gRNA [DCUg]), by controlling the Cas13a and gRNA expression with a nuclear factor κB (NF-κB)-specific promoter and U6 promoter, respectively. DCUg could specifically and effectively knock down the expression of reporter genes in the 293T and HepG2 cells. DCUg could also similarly knock down the expression of endogenous oncogenes (TERT, EZH2, and RelA) at both mRNA and protein levels in a human hepatoma cell HepG2, which led to significant apoptosis and growth inhibition. In contrast, the same transfection did not affect the target gene expression, cell apoptosis, and growth of a human normal liver cell HL7702. Finally, DCUg targeting these oncogenes was packaged into adeno-associated virus (AAV) and treated four cells (HepG2, HL7702, WEHI-3, and Hepa1-6) and tumor-bearing mice. As results, the recombinant AAV significantly inhibited the growth of three cancer cells (HepG2, Hepa1-6, and WEHI-3) in vitro and the xenografted Hepa1-6 and WEHI-3 tumors in mice. This study therefore developed a new tool for the CRISPR-Cas13a-based cancer gene therapy.